Development of TPACK-Integrated Creative Problem Solving Model in Improving Higher Order Thinking Skills - Edy Waluyo; Zamroni Uska (Jurnal Pendidikan Progresif, 2023)
Development of Creative Problem Solving Model integrated TPACK in Improving Higher Order Thinking Skills. Objective : This study aims to develop  creative problem solving model integrated TPACK to improve  higher order thinking skills. Methods : This research is Borg & Gall development with sample was 35 students of class XI SMAN 2 Selong. Research instruments is validation guidelines, practicality questionnaires and higher integral material essay tests. Data analysis using descriptive analysis for validity, practicality  and t test for effectiveness. Findings : Products in the category are valid according to experts materials, language and learning technology. The product is relatively practical with an average score of 82.63. The product is classified effective with t count = 98.54 > t table = 2.03 with α = 5% and N-Gain value of 0.77 with high category. Conclusion :  CPS model integrated TPACK has effective potential to improve higher order thinking skills. Keywords: creative problem solving,tpack, high order thinking.DOI: http://dx.doi.org/10.23960/jpp.v13.i2.202302